2015
DOI: 10.12659/msm.892822
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics in the Circle of Willis with Internal Carotid Artery Stenosis under Cervical Rotatory Manipulation: A Finite Element Analysis

Abstract: BackgroundThe circle of Willis (CoW) plays an important role in cerebral collateral circulation. The hemodynamics changes in the CoW have usually been associated with the internal carotid artery (ICA) stenosis, but whether rotatory manipulation will affect it remains unknown.Material/MethodsIn this study we attempted to analyze the influence of rotatory manipulation on the hemodynamics in the CoW in models with or without ICA stenosis by means of finite element analysis. For this purpose, the CoW was reasonabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…First, blood flow is increased in the ICA-PComA and the blood pressure is enhanced, leading to increased impact on the vessel wall ( 15 ). Furthermore, the membrane lacks the muscle layer in the blood vessel wall of the arterial bifurcation and the blood vessel wall appears to be thinning ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, blood flow is increased in the ICA-PComA and the blood pressure is enhanced, leading to increased impact on the vessel wall ( 15 ). Furthermore, the membrane lacks the muscle layer in the blood vessel wall of the arterial bifurcation and the blood vessel wall appears to be thinning ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…from more than 100 human arterial samples of CoW for FSI modeling [69]. The FSI models could simulate the blood flow in CoW [70] and its fluctuations under cervical rotator manipulation [71]. With in-vivo measurement of blood flow velocity by transcranial Doppler as inlet condition, capillary blood pressure as outlet condition, and age-related elastic modulus of arterial wall, Jahed et al investigated the effects of different hemodynamic and mechanical parameters (wall shear stress, blood pressure, mechanical stress, displacement) on the formation of aneurysms [72].…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…[70][71][72] Symons and Herzog 7 report vertebral artery strain during HVLA is less than that found in range of motion testing, and substantially less than the point of mechanical failure of the artery. Similarly, studies investigating occlusion have suggested the head position for a HVLA thrust has little impact on vertebral artery or internal carotid artery flow, [73][74][75][76] and that the duration of arterial occlusion during the application of an HVLA technique (100-150 milliseconds) is insufficient to effect blood flow to the brain. 77,78 A history of cervical spine trauma should also raise the suspicion of potential cervical spine instability and it has been suggested that there may be an association between this and internal carotid artery insufficiency.…”
Section: Accepted Manuscriptmentioning
confidence: 99%